Grafoil–Scotch tape-derived highly conducting flexible substrate and its application as a supercapacitor electrode. Issue 10 (1st March 2017) - Soni, Roby; Raveendran, Alka; Kurungot, Sreekumar
Abstract : Development of flexible supercapacitors is limited by the availability of flexible and durable conducting substrates; a conducting and cheap substrate for the active material deposition is essential for breakthrough progress in this direction. Abstract : Development of flexible supercapacitors is limited by the availability of flexible and durable conducting substrates; a conducting and cheap substrate for the active material deposition is essential for breakthrough progress in this direction. In this report, a highly flexible, conducting, and cheap substrate is prepared by simple stick and peel-off method involving Scotch tape and Grafoil. A Grafoil–Scotch tape derived flexible substrate exhibits a sheet resistance of 7 Ω □ −1 along with a high degree of flexibility and durability. Moreover, its properties are further enhanced by the anodization in order to increase the hydrophilicity and surface area. The substrate is highly thin with a thickness of just 74 μm. Its practical utility has been demonstrated by electrodepositing MnO2 as an active material and, thereafter, fabricating a solid-state flexible supercapacitor. The fabricated device exhibits high capacitance retention under bent (99%) and twisted (98%) conditions along with a low ESR of 7 Ω.